2012
DOI: 10.3892/etm.2012.553
|View full text |Cite
|
Sign up to set email alerts
|

Potential plasticity of T regulatory cells in pancreatic carcinoma in relation to disease progression and outcome

Abstract: Abstract. CD4+ CD25 + FoxP3 + regulatory T cells (Tregs) are understood to maintain peripheral tolerance to self-antigens and inhibit antitumor immune responses. However, compelling evidence suggests that, Tregs provide no anti-inflammatory protection in the tumor microenvironment, but rather contribute to a T helper 17 (Th17)-driven pro-carcinogenic process. Using three-color flow cytometry, we evaluated the percentage of circulating CD4 + CD25 + FoxP3 + Tregs in the peripheral blood of pancreatic carcinoma p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
62
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(66 citation statements)
references
References 45 publications
4
62
0
Order By: Relevance
“…However, functional studies of infiltrating T H 17 cells were not conducted in this study, and their increased recruitment may simply reflect known effects of IL-6. In addition, prior studies have correlated T H 17 cell infiltration and plasma IL-17A levels with poor prognosis in pancreatic cancer patients (He et al, 2011; Vizio et al, 2012). Nevertheless, it is clearly possible that IL-17 signaling may exert opposing influences on pancreatic tumorigenesis at different stages of the disease and in the context of variability in the host immune response.…”
Section: Discussionmentioning
confidence: 99%
“…However, functional studies of infiltrating T H 17 cells were not conducted in this study, and their increased recruitment may simply reflect known effects of IL-6. In addition, prior studies have correlated T H 17 cell infiltration and plasma IL-17A levels with poor prognosis in pancreatic cancer patients (He et al, 2011; Vizio et al, 2012). Nevertheless, it is clearly possible that IL-17 signaling may exert opposing influences on pancreatic tumorigenesis at different stages of the disease and in the context of variability in the host immune response.…”
Section: Discussionmentioning
confidence: 99%
“…The numbers of Th17 cells and expression of IL-17A are increased in human glioma (Hu et al, 2011) and esophageal cancer (Chen et al, 2012). Increased expression of IL-23, IL-17A and TGF-β1 signals adverse prognosis and predicts poor response to chemotherapy in pancreatic carcinoma (Vizio et al, 2012). Th17 cell abundance and IL-17 expression are also elevated in gastric cancer and indicate poor prognosis (Yamada et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…17,[24][25][26]31 One study showed a correlation between high IL-17 and improved survival in leukemia. 32 Four studies did not observe a significant correlation between high serum IL-17 levels and survival, [33][34][35][36] although one group did find a trend toward poor prognosis (p D 0.05). 36 Overall, a high amount of IL-17 protein in serum has predominantly been correlated with poor survival ( Table 2).…”
Section: Study Design and Selection Criteriamentioning
confidence: 92%